Innovative Approaches to Patient-Centered Care in Nursing - Nujud Mohammed Aljabri; Aishah Ail jaber Al mudawi; Shouq Hadi Mousa Kirbas; Reem Hussain Sufyani; Sabah Ali Jaber; Ashwag Naif Alrasheedi; Noura Saad Falah Alotaibi; Majed Assad Majed Assad; Monera Shalyial Al Enzi; Hashimyah Alawi Mohammed Al Radhi; Hamad Mohammed Hamad Alsaleh; Amnah Mohammed Yahia Megalei (International Journal of Medical Toxicology and Legal Medicine, 2024)
Growing interest in the promise of patient-centered care has led to numerous health care innovations, including the patient-centered medical home, shared decision-making, and payment reforms. How best to vet and adopt innovations is an open question. Washington State has been a leader in health care reform and is a rich laboratory for patient-centered innovations. the process of patient-centered care innovation undertaken by innovative health care organizations – from strategic planning to goal selection to implementation to maintenance.